Acute respiratory failure due to diffuse parenchymal lung diseases in a respiratory intensive care unit of North India - Sehgal, Inderpaul Singh; Agarwal, Ritesh; Dhooria, Sahajal; Prasad, Kuruswamy Thurai; Aggarwal, Ashutosh Nath; Behera, Digambar (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Acute respiratory failure (ARF) due to diffuse parenchymal lung diseases (DPLDs) is associated with high mortality. Whether ARF due to acute interstitial pneumonia (AIP), idiopathic pulmonary fibrosis (IPF) and non-IPF DPLDs behaves differently remains unclear. Methods: A retrospective analysis of consecutive DPLD subjects with ARF admitted to respiratory intensive care unit (RICU). The baseline clinical, demographic characteristics, cause of ARF and mortality were compared between the groups. Results: 145 (5.8% of RICU admission) subjects (mean [SD] age, 51.6 [14.7] years, 406% males) with DPLD-related ARF (17 AIP; 32 IPF; 96 non-IPF DPLD) were admitted. Common causes of ARF were acute exacerbation of the underlying DPLD (n=59, 40.4%) followed by infections (n=48, 37.5%). There was no difference in the peak, plateau and driving pressures across groups. The mortality rate was 45.5% (66/145) and was highest in AIP (82%) followed by IPF (59%) and non-IPF DPLD (34%). On multivariate logistic regression analysis, baseline APACHE II score, PaO2:FiO2 ratio, delta SOFA, and the use of invasive mechanical ventilation were independent predictors of mortality. The type of underlying DPLD however, did not affect survival. Conclusions: DPLD-related ARF is an uncommon cause of admission even in a RICU, and is associated with a high mortality.